CYBERLOAFING IN THE CONTEXT OF BIBLIOMETRIC ANALYSIS - SALİHOĞLU , Güneş Han (SSD Journal, 2022)
This aim is to search bibliometrically from the cyberloafing publications in the Dergipark database between 2012-2022. In this context, studies in the field of cyberloafing in the DergiPark database between 2012-2022 were carried out through excel and Maxqda program. 75 studies on the subject of loafing in the Dergipark database between 2012-2022 are bibliographically numbered. The basic indicators for the biblio are the formation of “publication metrics, number of authors and research management of articles according to the journals in which the articles are published”. According to the results of the research, there are a total of 61 different journals on the concept of cyberloafing. The history of the articles on cyberloafing by years There are 16 publications at the most in 2020 and 2 in 2012. The number of written articles is 14, the number of 2 articles is 44, the number of articles with three authors is 14, and the number of articles with four authors is 3, the number of articles with 14 authors and the article with four authors. According to the research method of the articles on cyberloafing, 67 beautifull8 exhibited. This counts only the plays published in the Dergipark database between 2012-2022. Therefore, different databases can be suggested to perform bibliometric analyzes of virtual environment applications. The examinations made will constitute the actions to be taken on the practice regarding this subject, such as the remaining sub-examination regarding the knowledge about cyberloafing.